Signal enhancement in cantilever magnetometry based on a co-resonantly coupled sensor - Körner, Julia; Reiche, Christopher F.; Gemming, Thomas; Büchner, Bernd; Gerlach, Gerald; Mühl, Thomas (Beilstein Journal of Nanotechnology, 2016)
Cantilever magnetometry is a measurement technique used to study magnetic nanoparticles. With decreasing sample size, the signal strength is significantly reduced, requiring advances of the technique. Ultrathin and slender cantilevers can address this challenge but lead to increased complexity of detection. We present an approach based on the co-resonant coupling of a micro- and a nanometer-sized cantilever. Via matching of the resonance frequencies of the two subsystems we induce a strong interplay between the oscillations of the two cantilevers, allowing for a detection of interactions between the sensitive nanocantilever and external influences in the amplitude response curve of the microcantilever. In our magnetometry experiment we used an iron-filled carbon nanotube acting simultaneously as nanocantilever and magnetic sample. Measurements revealed an enhancement of the commonly used frequency shift signal by five orders of magnitude compared to conventional cantilever magnetometry experiments with similar nanomagnets. With this experiment we do not only demonstrate the functionality of our sensor design but also its potential for very sensitive magnetometry measurements while maintaining a facile oscillation detection with a conventional microcantilever setup.
Keywords: cantilever magnetometry; coupled oscillator; iron-filled carbon nanotube; magnetometry; signal enhancement